Tourist purchases in a destination: What leads them to seek information from digital sources? - Alba García-Milon; Cristina Olarte-Pascual; Emma Juaneda-Ayensa; Jorge Pelegrín-Borondo (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - In a context where retail stores are closing down and high streets are declining, the purpose of this paper is to analyse on-site shopping by tourists. This work identifies the drivers that lead tourists to use digital information sources at the beginning of the shopping process. Understanding these drivers can help destination managers and retailers encourage tourists to shop. Design/methodology/approach - A personal survey was conducted in a Spanish city noted for its shopping facilities (Logro\~no), using a sample of 430 tourists with purchase intention. The survey was designed based on the extended unified theory of acceptance and use of technology (UTAUT2) model. A multivariate analysis, based on structural equation modelling, was carried out using partial least squares (PLS), based on variance. Findings - The study's finding is that performance expectancy, effort expectancy, social influence, facilitating conditions and habit influence intention to use digital sources of information to make purchases in a destination. Tourists prioritise utilitarian over hedonic motivations in the intention to use digital sources of information in tourist shopping. Originality/value - It has been recognised that tourists are the perfect target to revitalise on-site shopping and, therefore, destinations must provide attractive shopping experiences from the outset. Prior to purchase, the search for available information is the first stage of the tourist shopping journey. Although many studies have analysed tourist shopping behaviour, none have focused, using the UTAUT2, on the digital information sources tourists consult pre-purchase. This research develops understanding of tourist shopping behaviour in this new technological context. This can help retailers/destinations provide better services and optimise the shopper's experience from the first stage of the process.
Keywords: 650; Digital information sources; Logro\~no; Technology; Tourist shopping; UTAUT2